Religion, politics, and polarization how religiopolitical conflict is changing Congress and American democracy - D'Antonio, William V. (Lanham : Rowman & LIttlefield Publishers, 2013)
In Religion, Politics, and Polarization: How Religiopolitical Conflict are Changing Congress and American Democracy, three esteemed scholars trace the confluence of religion and party in the U.S. Congress over time. Drawing on forty years of congressional roll call votes as well as public opinion survey data, the book argues that the ideologies of both the Democratic and Republican parties are grounded in religious values and beliefs that strongly influence the voting patterns of party members. The authors examine several
Description based on print version record.
Keywords: United States. -- Congress; Legislators -- United States; Religion and politics -- United States; Church and state -- United States; POLITICAL SCIENCE / Government / Legislative Branch; Electronic books